Anidra And Its Management Through Ayurveda : A Review - Kuila , Jaya; Ghosh, Sukumar; Talapatra, Trisha; Ansari, Md Tanzil (International Research Journal of Ayurveda & Yoga, 2021)
Nidra (sleep) is considered as one among three Upastambhas (Pillars) of human life, others are Ahar (diet) and Brahmacarya (celibacy). Sufficient quantity and good quality of sleep (sound sleep) gives happiness, nourishment, strength, virility, knowledge and good quality of life. When there is difficulty in initiating or maintaining sleep or both and it may be due to inadequate quality or quantity of sleep, is called Anidra (Insomnia). The problem of insomnia increasing day by day due to stressful life, incompatible diet and faulty life style. People over the age of sixty-five years are affected more often than younger people. Anidra (Insomnia) associated with anxiety and stress may deteriorate memory and mental power. Physiological disturbances like cardiac disease, diabetes, blood pressure and psychological disturbances may be triggered with Anidra. Acharyas mentioned causative factors (that increase Vata and Pitta dosha), clinical features and different therapeutic approaches for the management of Anidra (Insomnia). Based on the Ayurvedic view the single herbs like Aswagandha (Withania somnifera), Jatamansi (Nardostachys jatamansi) etc., different compound formulations, Shodhan (Purification) therapies including the Pathya (wholesome) and Apathya (unwholesome) have been discussed in this article.